2020
DOI: 10.1155/2020/2343218
|View full text |Cite
|
Sign up to set email alerts
|

Jejunal Diverticulosis Probably Leading to Pylephlebitis of the Superior Mesenteric Vein

Abstract: Thrombophlebitis of the portal vein (pylephlebitis) is a rare but serious condition with a high mortality rate of 11-50%. A 56-year-old male patient presented with a two-day history of postprandial, colic-like epigastric pain, nausea, fever, chills, and diarrhea. Clinical workup showed peritonism, leukocytosis, and elevated C-reactive protein (CRP). A computed tomography (CT) scan revealed a long-segment, partial thrombosis of the superior mesenteric vein as well as gas in the portal venous system. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Articles published in languages other than English; cases where clinical, microbiological, or radiological studies did not support the diagnosis; case reports not providing an adequate amount of information, as well as those reporting non-human subjects were excluded from the analyses. The final number of articles included was 101, which resulted in total number of 103 patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Methodsmentioning
confidence: 99%
“…Articles published in languages other than English; cases where clinical, microbiological, or radiological studies did not support the diagnosis; case reports not providing an adequate amount of information, as well as those reporting non-human subjects were excluded from the analyses. The final number of articles included was 101, which resulted in total number of 103 patients [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ,…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that some bacteria among Acinetobacter, are opportunistic pathogens causing gastroenteritis such as Acinetobacter lwoffii and Acinetobacter johnsonii (Palmisano et al, 2020). Meanwhile, Morganella, Proteus, Veillonella, Actinomyces, Prevotella, Clostridium, Granulicatella were significantly enriched in the least one BNM, BCNM, or TCNM exposure group, which have been proved to be closely related to gastroenteritis (Hamilton et al, 2018;Li et al, 2018;Kiu et al, 2019;Bockmeyer et al, 2020;Iljazovic et al, 2021;Tian et al, 2022;Zhan et al, 2022). Accumulating evidence strongly suggests that intestinal dysbacteriosis and enteritis-associated pathogens bloom are important causes of intestinal inflammation, lesions, and even cancer (Gao et al, 2018;Khan et al, 2019;Liu et al, 2021).…”
Section: Discussionmentioning
confidence: 98%
“…This physio pathologic mechanism was proven in the 70s. The most common involved abdominal infection is colonic diverticulitis, then appendicitis and cholecystitis [2] . The incidence of septic thrombophlebitis of the porto-mesenteric veins due to acute appendicitis was close to 0.4% before 1950.…”
Section: Discussionmentioning
confidence: 99%